Yield and economics of intercropping legumes in maize (Zea mays) under rainfed conditions* - SAHU, BIRBAL (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was carried out during 2001-02 and 2002-03 to evaluate the yield and economics of maize (Zea mnays L.)-based intercropping systems under ramfed conditions Of jhabus hill maize was grown sole and intercropped with legumes (pigeonpea, soybean and blackgram) in 1 : 1 and 2:2 row spacing. The maize intercropped with soybean or blackgram in alternate rows (l:l),increased yield attributes of maize, viz cobslplant, length of cob, grainslcob, 1000- grain weight and grain yield (2 981 to 2 985 kg/ha) over the other systems. However grain yield was non significantly higher (3 015 kgka) when maize was grown alone. Further, maize + soybean either in 1:l or 2:2 rowr ratio performed equally well giving higher net return up to Rs 10 71 1 to.10 934 ha over the other intercropping systems including sole cropping of maize or legumes.